2015
DOI: 10.1186/s13046-015-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein modulates pRb2/p130 expression in human hepatocellular carcinoma cell lines through promoter methylation

Abstract: BackgroundHepatitis C Virus (HCV) infection is associated with chronically evolving disease and development of hepatocellular carcinoma (HCC), albeit the mechanism of HCC induction by HCV is still controversial. The nucleocapsid (core) protein of HCV has been shown to be directly implicated in cellular transformation and immortalization, enhancing the effect of oncogenes and decreasing the one of tumor suppressor genes, as RB1 and its protein product pRB. With the aim of identifying novel molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Most primary liver cancers are hepatocellular carcinoma (HCC). The some factors have been reported to contribute to HCC, such as aflatoxin, chronic hepatitis B virus infection, obesity, type 2 diabetes, heavy alcohol consumption, and smoking [ 3 , 4 ]. The treatments for HCC include surgical resection, liver transplantation and ablation, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Most primary liver cancers are hepatocellular carcinoma (HCC). The some factors have been reported to contribute to HCC, such as aflatoxin, chronic hepatitis B virus infection, obesity, type 2 diabetes, heavy alcohol consumption, and smoking [ 3 , 4 ]. The treatments for HCC include surgical resection, liver transplantation and ablation, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite no statistically signi cant relationships between pRb immunohistochemistry and prognosis have been observed, our results may suggest that mucinous BOTs, exhibiting low nuclear and high cytoplasmic levels of Rb2/p130, may potentially be considered the BOT histotype with a higher carcinogenic risk. In fact, loss of pRb2/p130 expression has been previously reported to inversely correlate with tumor grade and to be a poor prognostic indicator in several human cancers [14,14,16,18]. Moreover, its cytoplasmic localization, which implicates a loss of function, has been observed in several tumor types, including lymphoma and gastric cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Their most important target is the E2F-family of transcription factors which control the expression of genes that mediate G1-S transition [15,16]. The localization of these proteins into the nucleus or around the nuclear membrane has been shown at the molecular level during the different phases of the cell cycle [17,18]. In detail, during the cell progression through the S into the G2/M phases of division cycle, pRB undergoes phosphorylation, while in the late M phase, pRB is rapidly dephosphorylated.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators evaluated the epigenetic role of core protein in whole retinoblastoma (RB) family. They found that core‐induced DNMT1 and DNMT3B overexpression results in silencing two out of three RB family, such as pRb and pRb2/p130 in HuH‐7 core cells . Some of significant TSGs that highlighted to be implicated in HCV‐related HCC include secreted frizzled‐related protein (SFRP1), p16, E‐cadherin, RAR‐β2, etc.…”
Section: Hepatitis Cmentioning
confidence: 99%